Tranexamic Acid in Thoracic and Lumbar Fusions and Perioperative Blood Loss. Issue 10 (December 2019) - Wanderman, Nathan; Robinson, William; Carlson, Bayard; Bydon, Mohamad; Currier, Brad; Huddleston, Paul; Nassr, Ahmad; Freedman, Brett
Abstract : Study Design: This study was a retrospective cohort design. Objective: The objective of this study was to examine the impact of tranexamic acid (TXA) on total perioperative wound output following thoracic and lumbar spinal fusions. Summary of Background Data: TXA has been extensively studied with regard to intraoperative blood loss and transfusion rates. Few studies have looked specifically at the effect of TXA on postoperative drain output. Materials and Methods: We examined blood loss patterns in 617 consecutive adult patients undergoing lumbar and/or thoracic fusions at a single institution from January 2009 to 2016. These patients were divided into TXA and non-TXA, as well as high-dose and low-dose TXA, groups and analyzed using a propensity score to account for differences between cohorts. Results: The TXA and non-TXA groups were demographically similar. The mean number of levels fused was higher in the TXA group (4.8 vs. 3.1 levels, P <0.01). There was a significant reduction in both intraoperative blood loss (77.7 mL per level, P =0.020) and postoperative drain output (83.3 mL per level, P =0.002) in the TXA group when examined on a per level fused basis, but no significant difference without controlling for a number of levels. Postoperative blood loss tended to be higher in the TXA group for surgeries involving >5 levels fused. There was a significantly less blood loss in the high-dose TKA group both intraoperatively (296.4 mL per level fused, P <0.001) and postoperatively (133.4 mL per level fused, P <0.001). Conclusions: TXA significantly reduced both intraoperative and postoperative blood loss in lumbar and thoracic fusions when examined on a per level basis. However, with surgeries involving fusions >5 levels, TXA may increase postoperative drain output, with those losses offset by reduced intraoperative blood loss. High-dose TXA further reduced both intraoperative and postoperative blood loss as compared with low-dose TXA.